A checklist of the butterflies of Melanesia, Micronesia, Polynesia and some adjacent areas - Tennent, W. John (Zootaxa, 2006)
A systematic checklist of the butterflies of Melanesia, Micronesia and Polynesia is presented. A significant number of previously unpublished island records were found in major museum collections in the UK, Australia and the USA. Aspects of butterfly distribution, authorship of names, and taxonomy are addressed, and sources for about 2,200 published butterfly names are incorporated in a comprehensive bibliography of Pacific butterflies. Combined with recent publications dealing with specific areas, such as Papua New Guinea, a working systematic checklist of Pacific Region butterflies is available for the first time.